Direct observation of strong ion coupling in laser-driven shock-compressed targets. - Ravasio, A; Gregori, G; Benuzzi-Mounaix, A; Daligault, J; Delserieys, A; Faenov, A; Loupias, B; Ozaki, N; Rabec le Gloahec, M; Pikuz, T; Riley, D; Koenig, M (2007)
In this Letter we report on a near collective x-ray scattering experiment on shock-compressed targets. A highly coupled Al plasma was generated and probed by spectrally resolving an x-ray source forward scattered by the sample. A significant reduction in the intensity of the elastic scatter was observed, which we attribute to the formation of an incipient long-range order. This speculation is confirmed by x-ray scattering calculations accounting for both electron degeneracy and strong coupling effects. Measurements from rear side visible diagnostics are consistent with the plasma parameters inferred from x-ray scattering data. These results give the experimental evidence of the strongly coupled ionic dynamics in dense plasmas.